Ketentuan Daluwarsa Dalam Pertanggungjawaban Notaris Terhadap Akta Notariil Yang Dibuatnya - Yusita Permata Sari (Officium Notarium, 2021)
Notaries are responsible for authentic deeds which result in null and void at the end of their term of office. The need for limitations in the matter of the Notary's responsibility is because in civil law there are restrictions on prosecution. Article 1967 of the Civil Code explains that claims in civil law will be deleted after the 30-year time limit has passed. In this case, it creates uncertainty in terms of legal protection for the Notary as a Public Official after the end of his term of office and there is a blurring of norms in terms of determining the expiration time limit of the Notary's responsibility for the agreement he made in terms of Article 65 UUJN-P. There is a legal issue that is studied in this study, namely how the provisions on the expiration date of the Notary's accountability for the Notary deed he made. The author's purpose of doing this research is to identify and to analyze the expiration provisions in the Notary's responsibility for the notarial deed they made. The research method used is normative legal research, using a statutory approach, and a conceptual approach. The conclusion in this study is that UUJN does not regulate expiration, which means the Notary's lifelong responsibility regarding warkah, minutes of deed, and others. The difference between the 30 year expiration is completed with the Notary's accountability. The notary is responsible for being able to prove the truth of the deed in court when asked for informationKey Word: Notary, Expired, Responsibility AbstrakNotaris bertanggung jawab terhadap akta autentik yang berakibat batal demi hukum pada saat berakhir masa jabatannya. Perlunya limitasi dalam masalah tanggungjawab Notaris ini karena dalam hukum perdata terdapat pembatasan dalam penuntutan. Pada Pasal 1967 KUHPerdata menjelaskan, bahwa tuntutan dalam hukum perdata akan hapus setelah melewati batas waktu 30 tahun. Dalam hal ini menimbulkan ketidakpastian dalam hal perlindungan hukum bagi Notaris sebagai Pejabat Umum setelah berakhir masa jabatannya serta terdapat kekaburan norma dalam hal penentuan batas waktu daluwarsa pertanggungjawaban Notaris terhadap perjanjian yang dibuatnyaditinjau dari Pasal 65 UUJN-P. Ada isu hukum yang dikaji didalam penelitian ini yaitu bagaimana ketentuan daluwarsa dalam pertanggungjawaban Notaris terhadap akta Notariil yang dibuatnya. Tujuan penulis melakukan penelitian ini yaitu untuk mengetahui dan penulis akan menganalisis mengenai ketentuan daluwarsa didalam pertanggungjawaban Notaris terhadap akta notariil yang dibuatnya. Metode penelitian yang digunakan adalah penelitian hukum normatif, menggunakan pendekatan peraturan perundang-undangan, dan pendekatan konseptual. Kesimpulan dalam penelitian ini adalah UUJN tidak mengatur mengenai daluwarsa, yang berarti tanggungjawab Notaris seumur hidup mengenai warkah, minuta akta, dan lain-lain saja. Berbeda antara daluwarsa waktu 30 tahun selesai dengan pertanggungjawaban Notaris. Notaris bertanggungjawab untuk dapat membuktikan kebenaran akta dalam pengadilan apabila dimintai keterangan.Kata-kata Kunci: Notaris, Daluwarsa, Tanggungjawab